ON WINGS OF FATE - Mekathoti, Hemanth Kumar; Mindi, Thriveni (International Journal of Psychosocial Rehabilitation, 2020)
The role women in today’s world are equal to men but she is not allowed to enjoy the pleasure of the same prominence on par with her counterpart men. Her education and career do not redeem her from the familial obligations. Her potentialities are at stake as she has to attend at home and strive to design a promising career. The elementary nature that makes the women all over the world is the same but they seem to differ in their expression due to the varied societal conventions and background of their countries.Many contemporary women novelists dealt with the themes of women but Kavery Nambisan’s focus deemed deep into the issues of woman’s problems. She believes that writers should deal with the themes regarding the internal problems of India especially the problems related to the social status of women rather than dealing with the continental and global issues and themes like alienation, exile, and globalization. The novels of Kavery Nambisan aptly examine and exemplify the sufferings of women. Kavery Nambisan’s On Wings of Butterflies signifies that the wings of butterfly are like the aims, goals and the desirable needs of women which are still not satisfied. It justifies that the women folk are like butterflies that deserve the freedom which they as human beings are entitled to and they should equally be treated on a par with the men clan.